1979
DOI: 10.1111/j.1651-2227.1979.tb05024.x
|View full text |Cite
|
Sign up to set email alerts
|

Cow's Milk Allergy, Incidence and Pathogenetic Role of Early Exposure to Cow's Milk Formula

Abstract: A study was performed in infants under the age of 12 months born during 1974 and admitted to St. Göran's Children's Hospital with symptoms suggestive of cow's milk allergy (CMA). The aims of the study were to determine the role of early exposure to cow's milk formulas as a predisposing factor to CMA and to estimate the incidence of CMA in infancy. Twenty-five infants fulfilled the criteria for CMA. Available records were reviewed and a careful history was obtained from the mothers on two occasions. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 7 publications
4
37
0
1
Order By: Relevance
“…As already reported (Nespoli et al, 1993), we have found an increased incidence of IgG antibodies to beta-lactoglobulin in the serum of people with Down syndrome compared with a control group, and an incidence which overlaps that of the general population (Walker-Smith, 1975;Stintzing & Zetterstrom, 1979;Host, 1994). Our most interesting result is the 100% specificity of IgG antibodies to beta-lactoglobulin for the diagnosis of CMPI and the increased frequency below age 5 years.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As already reported (Nespoli et al, 1993), we have found an increased incidence of IgG antibodies to beta-lactoglobulin in the serum of people with Down syndrome compared with a control group, and an incidence which overlaps that of the general population (Walker-Smith, 1975;Stintzing & Zetterstrom, 1979;Host, 1994). Our most interesting result is the 100% specificity of IgG antibodies to beta-lactoglobulin for the diagnosis of CMPI and the increased frequency below age 5 years.…”
Section: Discussionsupporting
confidence: 71%
“…Its incidence ranges from 0.3 to 7.5%, depending upon diagnostic criteria and clinical features (Walker-Smith, 1975;Stintzing & Zetterstrom, 1979;Host, 1994). The absence of a reliable and specific test and the large variability of symptoms has produced many different diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are agedependent, as CMA is acquired in early life and lost later on. A combination of massive exposure to CM proteins and deficient local production of immunoglobulins (87, 97), which takes place when infants are not breast fed at all, favours excessive absorption of CMA antigen ( 1 17), and later such children frequently show CMA (25,108). Other conditions that lead to increased CM antigen absorption have been reported to precede the clinical symptoms of CMA: infective gastroenteritis, prematurity, and surgery of the gastrointestinal tract (47, 92).…”
Section: Eosinophils In C M Amentioning
confidence: 99%
“…Incidences of 0.5–7.5% of newborn or young children suffering from milk allergy, i.e. with immediate-type reaction symptoms, have been reported [1, 2]. Most other studies have stated an average incidence of 2–3% in the whole population of infants under 1 year of age [3, 4].…”
Section: Introductionmentioning
confidence: 99%